Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

The Impact of COVID-19 on women - United Nations (United Nations Entity for Gender Equality and the Empowerment of Women (UN Women); United Nations Secretariat, 2020)
The year 2020, marking the twenty-fifth anniversary of the Beijing Platform for Action, was intended to be ground-breaking for gender equality. Instead, with the spread of the COVID-19 pandemic, even the limited gains made in the past decades are at risk of being rolled back. The pandemic is deepening pre-existing inequalities, exposing vulnerabilities in social, political and economic systems which are in turn amplifying the impacts of the pandemic. Across every sphere, from health to the economy, security to social protection, the impacts of COVID-19 are exacerbated for women and girls simply by virtue of their sex. This policy brief by the UN Secretary-General explores how women and girls’ lives are changing in the face of COVID-19, and outlines suggested priority measures to accompany both the immediate response and longer-term recovery efforts.
Keywords: 2000 à aujourd'hui; 2020-2029; covid-19; discipline; droit; droits des femmes*; droits humains; pandémie; projet charge mentale; périodes historiques; santé; science politique et droit; thématiques; violences; violences sexistes et sexuelles

Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge handbooks, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Les droits sexuels des personnes handicapées: réflexion sur le développement du droit international - Mona Paré (Genre, Sexualité et Société, 2018)
Interest in the sexuality of persons with disabilities is growing and research improves our understanding of issues in this regard. This leads us to a reflection on the definition of sexual rights in international law, and the way in which sexual rights of persons with disabilities are understood. Examining existing norms leads to the conclusion that despite developments in this area, sexual rights remain largely limited to the field of health, and this has not changed with the adoption of the Convention on the Rights of Persons with Disabilities (CRPD). The limited claims related to these rights during the negotiations of the CRPD is surprising given the significant participation of persons with disabilities. Yet, despite the lack of clarification in relation to the sexual rights of persons with disabilities in the convention, the practice of interpretation of law remains a way to develop international law in this field, particularly through the evolving concept of non-discrimination.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; approches et analyses; capacitisme; cours; discipline; droit; droit des personnes en situation de handicap; droit international; histoire et politique; militance; premier cycle; périodes historiques; ressource en ligne; santé; science politique et droit; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap

(Re)penser l’accès aux espaces intimes en contexte de handicap intellectuel: une question de droit et de participation sociale - Pariseau-Legault, Pierre; Holmes, Dave (Revue générale de droit, 2017)
En contexte de handicap, la question de l’accès est constituée généralement de l’éventail des aménagements individuels et collectifs nécessaires afin de faciliter l’occupation d’espaces publics. A contrario, peu de choses sont dites à propos des aménagements possibles et potentiels requis afin de sécuriser l’espace privé des personnes identifiées comme ayant un handicap intellectuel. Ce sont pourtant ces lieux intimes, au sein desquels se développent et se déploient l’identité et l’expression affectives, qui sont susceptibles de contribuer à une reconnaissance plus soutenue de l’identité affective et de la citoyenneté sexuelle de ces personnes. Inspirée par les théories d’Erving Goffman et de Michel Foucault, une analyse phénoménologique interprétative (API) fut réalisée auprès des personnes ayant un handicap intellectuel et de leurs proches aidants afin d’explorer cette situation. Nos constats préliminaires suggèrent l’existence d’un processus de négociation complexe des acteurs, des lieux et des moments nécessaires afin de favoriser le développement de la vie affective et sexuelle. De ce fait, trois modes d’existence semblent cohabiter au sein d’une matrice complexe : la dépossession, l’habitation et l’occupation des espaces de socialisation et d’expression affective. Il est proposé d’aborder cette problématique en tant que dynamique géopolitique intégrant les processus d’exclusion des pratiques sexuelles des espaces privés, leur projection dans des espaces publics et, finalement, la juxtaposition de ces deux sphères, publique et privée dans des espaces mixtes. Nous discuterons enfin des implications de cette réflexion sur la « question de l’accès » et sur les politiques publiques visant à diminuer la discrimination systémique ciblant les personnes identifiées comme ayant un handicap intellectuel.
Keywords: approches et analyses; capacitisme; care; corps; cours; discipline; droit; histoire et politique; inégalités; justice sociale; premier cycle; ressource en ligne; santé; science politique et droit; science politique et droit de la santé; sciences; sciences de la santé; sciences politiques; sex1920; sexualité; systèmes d'oppressions; thématiques

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques

Beyond Gratification:The Benefits of Pornography and the Demedicalization of Female Sexuality - Jeneanne Orlowski (The Modern American, 2012)
This Paper argues that non-obscene adult pornography should remain protected by the United States Constitution because it has contributed to the demedicalization of female sexuality. There is an ongoing debate among feminists regarding the value of pornography and whether it should be protected under the First Amendment. This Paper explains the background of the debate regarding the status of pornography as a form of speech and whether it has value that warrants its protection. Specifically, this Paper focuses on the removal of nymphomania from the Diagnostic and Statistical Manual and its absence as a modern medical diagnosis as an example of the demedicalization of female sexuality. The demedicalization of female sexuality has positively affected women in the United States. Catalysts for this demedicalization include the production and consumption of adult pornography by women. For this reason, adult pornography deserves continued protection as a form of free speech under the First Amendment.
Keywords: amériques; corps; cours; discipline; droit; droits des femmes*; premier cycle; régions géographiques; santé; science politique et droit; sex1911; sexualité; sofia; thématiques; états-unis

Invisibilité des lésions professionnelles et inégalités de genre : le rôle des règles et pratiques juridiques - Lippel, Katherine; Cox, Rachel (Santé au travail : approches critiques, 2012)
Keywords: amériques; canada; discipline; droit; projet charge mentale; ressource en ligne; régions géographiques; santé; santé au travail; science politique et droit; thématiques; travail

Women, gender equality and climate change - United Nations (2009)
Detrimental effects of climate change can be felt in the short-term through natural hazards, such as landslides, floods and hurricanes; and in the long-term, through more gradual deg radation of the environment. The adverse ef fects of these events are already felt in many areas, including in relation to, inter alia, ag riculture and food security; biodiversity and ecosystems; water resources; human health; human settlements and migration patterns; and energy, transport and industry. In many of these contexts, women are more vulnerable to the effects of climate change than men—primarily as they constitute the majority of the world’s poor and are more dependent for their livelihood on natural re sources that are threatened by climate change. Furthermore, they face social, economic and political barriers that limit their coping ca pacity. Women and men in rural areas in developing countries are especially vulnerable when they are highly dependent on local natural resources for their livelihood. Those charged with the responsibility to secure water, food and fuel for cooking and heating face the greatest challenges. Secondly, when coupled with unequal access to resources and to decision-making processes, limited mobility places women in rural areas in a position where they are disproportionately affected by climate change. It is thus important to identify gender-sensitive strategies to respond to the environmental and humanitarian crises caused by climate change.1
Keywords: 2000 à aujourd'hui; 2000-2009; changements climatiques; discipline; droit; développement international; environnement; femmes agricultrices; projet charge mentale; périodes historiques; santé; science politique et droit; sécurité alimentaire; thématiques; travail

A broader vision of the reproductive rights movement: Fusing mainstream and latina feminism - Hooton, Angela (American University Journal of Gender, Social Policy & the Law, 2005)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; femmes* latino-américaines; histoire et politique; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; santé reproductive; science politique et droit; systèmes d'oppressions; thématiques; états-unis

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Science, conscience et action : vingt-cinq ans de recherche féministe au Québec - Dagenais, Huguette (Les éditions du remue-ménage, 1996)
Après un quart de siècle de néoféminisme, on connaît encore mal la recherche féministe et l’ampleur du travail accompli par ces chercheuses. Les auteures examinent ici les travaux qui ont porté sur la famille, la conciliation travail-famille et sur l’emploi, ceux qui ont documenté des aspects particuliers de la santé des femmes et de la violence conjugale ainsi que les nombreuses études produites dans le domaine de l’éducation. Elles mettent également en lumière les changements et les résistances révélés par les recherches dans le champ religieux, le champ politique, celui du droit de même que dans le domaine des communications. Ce faisant, elles rendent manifestes les caractéristiques de la recherche féministe québécoise, notamment les liens établis par les chercheuses entre théorie et pratique, recherche et action. Des textes de Pierrette Bouchard, Anita Caron, Renée Cloutier, Christine Corbeil, Huguette Dagenais, René B.-Dandurand, Francine Descarries, Louise Guyon, Thérèse Hamel, Geneviève Martin, Karen Messing, Josée Néron, Ann Robinson, Armande Saint-Jean, Diane-Gabrielle Tremblay et Manon Tremblay.
Keywords: 1900-1999; amériques; conciliation famille-travail; cours; discipline; droit; famille; fem1000; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; santé; science des religions; science politique; science politique et droit; sciences humaines; thématiques; théologie; violences; violences contre les femmes*